Pengembangan Unit Usaha Tempe melalui Aplikasi Mesin Giling Kedelai Teknologi Screw - Rela Adi Himarosa; Sudarisman Sudarisman; Ammaru Bisandyaloka; Fajar Sofyantoro (Jurnal Pengabdian Pada Masyarakat, 2022)
DEVELOPMENT OF TEMPE PRODUCTION UNIT THROUGH THE APPLICATION OF SOYBEAN SCREW-TYPE MILLING MACHINES. Pondok Pesantren Asy-Syifa’ Muhammadiyah (PPAM), located in Yogyakarta, aims to become an independent and benevolent institution for the community. To realize its noble missions, PPAM initiated the Tempe Production Unit (TPU) as an alternative source of financial incomes and to provide nutritional foods for its students. The TPU at PPAM was established through the application of the screw-type milling machine, which is more efficient, time-saving and hygienic compared to traditional milling methods. The community service program at PPAM was initiated by involving the administrators in an intensive discussion to analyze the required resources and future prospects of TPU. The manufacturing process of milling machine was carried out at Universitas Muhammadiyah Yogyakarta, followed by training of the PPAM members in operating the milling machine. The PPAM members enthusiastically participated and provided valuable inputs for the machine adjustments. Before officially handing the milling machine to PPAM, the machine has been adjusted in accordance with the PPAM members suggestions. Evaluation and monitoring were carried out during the initial production stages, which has been successfully processing 4 kg of soybeans into 20 packs of tempeh per day.